Commissions of Inquiry as a Response to Crisis: The Role of the Jali Commission in Creating Public Awareness of Corruption (Part 1) - Stephen Allister Peté (Obiter, 2021)
When the government of a liberal constitutional democracy is confronted by some or other existential crisis that threatens a major institution of state or the very foundations of the democracy itself, it will often appoint a high-level judicial commission of inquiry as part of its response to the crisis. South Africa is no exception to this tendency, as is evidenced in recent years by the appointment of no fewer than four such commissions in response to a series of crises related to ongoing corruption within state institutions – commonly referred to by ordinary South Africans as “state capture”. This has raised questions as to the alleged benefits of such commissions when viewed in relation to their considerable costs. This article seeks to contribute to this general debate by focusing on one of the purported benefits of such commissions that may be somewhat under-appreciated. This is the creation of public awareness, during the life of the commission itself, about the nature and extent of the particular grave threat that confronts the society in question. It is contended that, mediated by a free and vibrant press, the public narrative that emerges during the operation of a commission of inquiry may serve to make a liberal democratic society more resilient in the face of threats to that society’s continued existence. This article seeks to support this contention by focusing on an important precursor to the more recent commissions of inquiry on corruption in South Africa – that is, the Jali Commission of Inquiry into corruption within the South African penal system, which sat in the early years of the new millennium. By analysing the many articles and reports that appeared in a range of South African newspapers during the initial hearings of the Jali Commission, this article documents the emergence of an important public narrative on corruption within South Africa’s prisons, and reflects upon the ultimate significance of this narrative. This article is divided into two parts: the first part deals with the initial hearings of the Jali Commission in KwaZulu-Natal, and the second part with subsequent hearings in the Free State.